2021
DOI: 10.3390/cancers13092232
|View full text |Cite
|
Sign up to set email alerts
|

PBK/TOPK: An Effective Drug Target with Diverse Therapeutic Potential

Abstract: T-lymphokine-activated killer cell-originated protein kinase (TOPK, also known as PDZ-binding kinase or PBK) plays a crucial role in cell cycle regulation and mitotic progression. Abnormal overexpression or activation of TOPK has been observed in many cancers, including colorectal cancer, triple-negative breast cancer, and melanoma, and it is associated with increased development, dissemination, and poor clinical outcomes and prognosis in cancer. Moreover, TOPK phosphorylates p38, JNK, ERK, and AKT, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 129 publications
(176 reference statements)
4
21
0
Order By: Relevance
“…T-lymphokine-activated killer-cell-originated protein kinase (TOPK), also known as PDZ-binding kinase (PBK), is a novel mitotic serine/threonine protein kinase, which was confirmed to be associated with the development, progression, and metastasis of malignancies and to be a potential therapeutic target in cancer therapy [ 30 ]. Studies have shown that PBK expression is increased in various cancers compared with normal tissues [ 31 ]. In this study, we explored the expression of PBK in pan-cancers using oncomine and TIMER databases.…”
Section: Discussionmentioning
confidence: 99%
“…T-lymphokine-activated killer-cell-originated protein kinase (TOPK), also known as PDZ-binding kinase (PBK), is a novel mitotic serine/threonine protein kinase, which was confirmed to be associated with the development, progression, and metastasis of malignancies and to be a potential therapeutic target in cancer therapy [ 30 ]. Studies have shown that PBK expression is increased in various cancers compared with normal tissues [ 31 ]. In this study, we explored the expression of PBK in pan-cancers using oncomine and TIMER databases.…”
Section: Discussionmentioning
confidence: 99%
“…TOPK may promote the occurrence and development of In addition, we also found that HI-TOPK-032 could inhibit the phosphorylation of p38 MAPK. TOPK, as a serine-threonine kinase, belongs to the MAPKK family and is closely associated with a variety of biological activities (47). TOPK has been reported to play a role in the cell cycle regulation and mitosis process and become active during mitosis to phosphorylate Thr9 residues of CCNB1/CDK1 (48).…”
Section: Discussionmentioning
confidence: 99%
“…This non-concordance may be explained by differences between individual molecular subtypes, especially in the case of FOXA1 , which directs luminal differentiation. These genes in addition comprise PBK (encoding a protein kinase also known as TOPK with a broad spectrum of targets, including histones [ 121 ]) and HJURP , encoding a chaperone for centromeric variant histones. Intriguingly, a sole publication on bladder cancer so far implicates HJURP in the regulation of PPARÎł and SIRT1 [ 122 ].…”
Section: Alterations Of Chromatin Regulator Genes In Urothelial Carcinomamentioning
confidence: 99%